The work challenges faced by primary healthcare workers in Guangzhou during the COVID-19 pandemic prevention and control period of 2021–2022: a qualitative study - Jin, Yuqing; Feng, Huiyao; Xiao, Qin; Tian, Fenglin; Yao, Huan; Zhang, Runquan; Wu, Qiqi; Zhu, Haiyuan; Zheng, Wanshan; Chen, Jin; Liu, Tao; Ma, Wenjun; et al. (Frontiers in Public Health, 2024)
Background: Since the outbreak of COVID-19, primary healthcare workers in China have played an irreplaceable and positive role in the work of epidemic prevention and control. Their hard work and selfless dedication are key factors in achieving effective control of the epidemic. However, the suddenness, uncertainty, and high transmissibility of the epidemic have brought unprecedented challenges to grassroots epidemic prevention work. This paper conducts an in-depth analysis of the work of primary healthcare workers in Guangzhou City during the period of COVID-19 2 epidemic prevention and control, revealing the main difficulties and challenges they face in epidemic prevention and control.Background:Primary healthcare workers in China were vital in controlling COVID-19, facing unprecedented challenges due to the pandemic's suddenness and transmissibility. This paper analyzed their work in Guangzhou, highlighting key difficulties in past epidemic control efforts.Methods: Qualitative interviews were conducted with pandemic prevention and control personnel at primary healthcare institutions in Guangzhou, utilizing a semi-structured interview outline to gather data on the challenges and difficulties encountered by primary healthcare workers during the COVID-19 pandemic.Interview recordings were transcribed into text, and grounded theory techniques were employed to extract significant information for coding. The derived codes were then inductively categorized and classified to establish themes.Methods:Semi-structured qualitative interviews were conducted with selected primary healthcare workers in Guangzhou City and audio-recorded until saturation of themes was reached. The data were analyzed independently for themes using NVivo V.12.Results: Thematic analysis of qualitative interview data revealed that challenges and difficulties encountered in grassroots epidemic prevention and control work during the COVID-19 pandemic were primarily categorized into seven dimensions: human resource allocation, material and vehicle support, epidemic prevention subsidies and compensation, humanistic care, upper-level management, horizontal collaboration, and resident cooperation.Based on the findings, the research team recommends that administrative departments and institutions related to primary healthcare should appropriately schedule personnel work and rest time, adjust work content flexibly, optimize the allocation of medical and logistical resources, and increase investment in primary healthcare work as well as staff protection.